Lexicon of Medicinal Plants in Pangkep Regency, South Sulawesi - Amir, Amriani (Arus Jurnal Sosial dan Humaniora, 2025)
Traditional knowledge of medicinal plants constitutes an important part of local wisdom that is closely intertwined with regional language and cultural practices. In Pangkep Regency, South Sulawesi, such knowledge is preserved through the Makassar language and continues to be applied in traditional medical treatments. This research employed a qualitative descriptive method, with data collected through in-depth interviews with community elders, traditional healers (sandro), and local residents possessing extensive ethnomedicinal knowledge. Lexical semantic analysis was used to identify medicinal plant names, morphological parts utilized, lexical meanings, and therapeutic functions. The findings document 57 medicinal plant lexicons that remain actively used by the community and are classified based on the plant parts employed, including leaves, fruits, rhizomes, flowers, seeds, roots, stems, sap, leaf gel or mucus, pods, and marine algae thallus. Leaves were the most frequently utilized plant part, followed by fruits and rhizomes, indicating considerations of accessibility, sustainability, and ease of processing. The presence of marine algae as medicinal resources reflects the coastal ecological context of Pangkep Regency. Furthermore, lexical analysis reveals that plant naming patterns are shaped by physical characteristics, color, taste, habitat, and perceived efficacy, highlighting the close relationship between language, environment, and traditional knowledge. This research contributes to the documentation and preservation of ethnobotanical knowledge and emphasizes the role of regional languages in sustaining cultural heritage and biodiversity conservation.